Analysis of Workplace Stress and Organizational Performance in Human Resource Management: A Case Study of Air Traffic Controllers of Pakistan (International Journal of Management and Sustainability, 2014)
Today main issue in management and organization is corporate sustainability which includes organizational performance. Organizational performance is one of the strategic issues for any management. The purpose of the study is to investigate the relationship between workplace stress and organizational performance; and mediational affect of employees’ health issues between workplace stress and organizational performance. Both primary and secondary data were used for the current study. A self-developed questionnaire was used after validating it through a pilot study for collecting the data. Proportionate random sampling technique was used to select the sample – air traffic controllers. The hypotheses were accepted at significant ‘p’ value proving the model as good fitting. Out of 134 questionnaires, 122 were received back from the respondents and used for the current study. The study results confirm that there is a negative relationship between workplace stress and organizational performance; while there is a partial mediational affect of employees’ health issues between workplace stress and organizational performance. The quantitative technique was used for investigation of the problem. The practical implications of the paper include implementation of the results provided by the researcher to reduce workplace stress by providing appropriate health facilities to the subjects; and increasing organizational performance. The findings of this study are important for corporations and future researchers on organizational behavior field. Original finding have a potential to contribute related field and expecially aviation management and strategy since sever workplace stress has an direct impact on both performance and employee sustainability in aviation business. The research aims to raise awareness of organizational behavior to achieving business objectives since human resource is most critical risk on the way of corporate sustainability.